Longitudinal Myelitis of a Neuro-Behçet Patient - Qi TANG,; Jing TIAN, (Archives of Rheumatology, 2016)
Behçet’s disease is a chronic, relapsing inflammatory disorder of unknown etiology. Neuro-Behçet’s disease (NBD) occurs in approximately 5 to 49% of patients with Behçet’s disease. Spinal cord involvement is very rare in NBD. In this article, we report a 22-year-old male patient of NBD with longitudinal myelitis involving the entire spinal cord. Patient was admitted with one-week of headache, vomiting, and urinary incontinence. Before admission, he felt motor weakness for two years and had noticed recurrent genital and oral ulcers with a frequency of more than three episodes per year for five years. T2-weighted spinal magnetic resonance images showed hyperintensities within the entire spinal cord. He was diagnosed as NBD with longitudinal myelitis. Intravenous methylprednisolone (120 mg/day) was administered for three days, followed by an oral administration of prednisolone (45 mg/day). In conjunction with the steroid therapy, intravenous cyclophosphamide (0.4 g/week) was administered twice. Rapid improvements were detected after receiving treatments for half a month. NBD associated longitudinal myelitis is really rare. This case provided important implications for the diagnosis and treatment of longitudinal myelitis in NBD patients.